Tindak Tutur Direktif Masyarakat Petani Cengkeh pada Guyub Tutur Adonara Tengah Flores Timur - Yasinta Paulina Odjan; Alexander Bala (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
This study provides an overview of the speech acts of the farming community in Kokotobo Village, Adonara Tengah District, East Flores Regency. The purpose of this writing is to find data and a clear picture of how the directive actions of the farmer community in Kokotobo Village, Adonara Tengah District, East Flores Regency. The method used is the method of engaging free listening proficiently. The technique used is observation, record and note, while the theory used is pragmatic theory. The results of this study indicate that in the directive speech act of the farmer community in Kokotobo Village, Adonara Tengah District, East Flores Regency, it was found: (1) the form of directive speech instructs, the form of advising, the form suggests (2) the meaning of the act said the mutual directive, the meaning of information (3) the speech act function of the request directive, the question function, the command function and the advice function.